2020
DOI: 10.4315/jfp-19-520
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Klebsiella pneumoniae: Virulence Potential, Antibiotic Resistance, and Risks to Food Safety

Abstract: ABSTRACT Gastrointestinal carriage of Klebsiella pneumoniae is a predisposing factor for liver abscess in several Asian countries. To determine whether hypervirulent K. pneumoniae in the gut may be transmitted through food, we screened a range of raw and ready-to-eat retail food by culture and recovered K. pneumoniae in 21% (147 of 698) of samples tested. Based on PCR, no K. pneumoniae isolates carried the rmpA gene linked to commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 43 publications
1
33
1
Order By: Relevance
“…Asymptomatically colonizing strains of capsular serotype K1 Klebsiella pneumoniae sequence type 23 (ST23) have been reported as related to liver abscess in South Korea ( 1 , 2 ) and recently in the United States ( 3 ). In Europe, the colonization of healthy volunteers by K. pneumoniae of high clonal diversity genetic lines is not associated with severe infections ( 4 ).…”
Section: Announcementmentioning
confidence: 99%
“…Asymptomatically colonizing strains of capsular serotype K1 Klebsiella pneumoniae sequence type 23 (ST23) have been reported as related to liver abscess in South Korea ( 1 , 2 ) and recently in the United States ( 3 ). In Europe, the colonization of healthy volunteers by K. pneumoniae of high clonal diversity genetic lines is not associated with severe infections ( 4 ).…”
Section: Announcementmentioning
confidence: 99%
“…However, urinary tract infections were caused by uropathogenic E. coli (Parajuli et al, 2017). Furthermore, K. pneumoniae is an opportunistic pathogen associated with foodborne disease outbreaks (Hartantyo et al, 2020). It causes extraintestinal human infections such as urinary tract infection, bloodstream infection (septicemia), pneumonia, pyogenic liver abscess (Davis & Price, 2016; Martin et al, 2016), and gastrointestinal diseases (Sun et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Our study revealed the presence of K. pneumoniae in cooked food from private and public restaurants. According to the Public Health Agency of Canada [28] and Sri Harminda et al [29], this may result from its thermotolerance. These authors found that complete inactivation of the bacteria may not always occur at 60°C.…”
Section: Discussionmentioning
confidence: 99%